SPATIAL THINKING FOR INNOVATION: THE LEONARDO-MAXWELL-EINSTEIN METHOD, REVIVED - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
Free-running spatial intuition is like analog computation: it is indispensable for scientific progress despite its intrinsic inaccuracy. Do return to the first beginnings of a gold vein, was Maxwellâ€™s advice. Returning to the gold vein of Einsteinâ€™s â€œhappiest thoughtâ€ leads to three other shiny results. Many accepted findings crumble as the barefoot method shows its mettle. A new cosmology is implicit and so is a new source of energy.